The Effect of Covering Media Composition and Fertilizer Cow Manage on The Growth of Palm Oil (Elaeis Guineensis J.) Seeds in Pre-Nursery - Jamidi1; Irawan, Dicky; Purba, Mhd. Yudistira Pratama (Jurnal Online Pertanian Tropik, 2021)
The impact of using humus as a medium for planting oil palm seeds continuously canreduce the availability of humus in the field. Therefore, the use of subsoil as a plantingmedium and the use of cow manure are expected to increase the growth of oil palmseedlings. The purpose of the study was to determine the effect of the composition ofthe planting medium on the growth of oil palm seedlings. The research was conductedin Simalas Village, Serdang Bedagai, North Sumatra. The research method used was a 2factor randomized block design with 9 treatments and 3 replications. The results showedthat topsoil and subsoil planting media with a ratio of 1:1 had an effect on increasingplant height and leaf number of oil palm seedlings, while the application of cow manure25 g/polybag also had an effect on increasing the number of leaves of oil palmseedlings. There is a treatment interaction between the composition of the plantingmedium and cow manure on the number of leaves of oil palm seedlings.